Opakovaná sterilizace artikulačních komponent kloubních náhrad etylenoxidem nemá vliv na strukturu a vlastnosti UHMWPE - Fulín, Petr; Šlouf, Miroslav; Gajdošová, Veronika; Němeček, P; Krejčíková, Sabina; Pokorný, David (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY In clinical practice UHMWPE is the most commonly used material for manufacturing articular components of joint replacements. The purpose of this study is to find out whether repeated ethylene oxide sterilization results in oxidative degradation of UHMWPE or not and also whether the oxidative degradation of various types of ethylene oxide-sterilized UHMWPE depends on storage time or not. MATERIAL AND METHODS The set included 12 samples of UHMWPE (three samples with different modifications (virgin PE, with E vitamin and cross-linked with thermal treatment) and different number of sterilizations (0×-3×)). The set also included 8 samples of commercial components of hip or knee replacements sterilized with ethylene oxide and stored for different storage periods. The oxidative degradation was assessed by infrared microspectroscopy, based on which the oxidation index (OI), transvinylene index (VI), crystallinity index (CI) and E vitamin index (EI) were calculated. Mechanical properties of UHMWPE were obtained through microhardness measurements. Statistical processing of the results was performed. RESULTS In all the samples, very low oxidative degradation values were reported (most OI values < 0.1). All radiation crosslinked UHMWPE samples showed an increased VI index and a slightly lower crystallinity index. All unmodified samples (irrespective of whether or not and how many times or how long ago the samples were sterilized with EtO) had almost zero value of VI. Changes in crystallinity were negligible (in the rage of 0.56-0.63), which required very accurate measurements of micromechanical properties. Yet, linear correlation was established between microhardness and crystallinity. DISCUSSION All the mentioned indices changed as anticipated: OIs were very low and slightly increased with time of storage, VIs of radiation crosslinked samples grew in proportion to the total gama radiation dose, CIs decreased in samples thermally treated by remelting, and EIs were very low due to negligible concentration of stabiliser (0.1%) in the samples of medical grade UHMWPE. CONCLUSIONS All samples showed zero or minimum oxidative degradation. This confirmed that neither ethylene oxide sterilization, nor multiple EtO sterilization or longer storage of polymer after ethylene oxide sterilization result in major oxidative degradation. Key words: UHMWPE, ethylene oxide, sterilization, oxidation, infrared spectroscopy, microhardness.
Keywords: vitaminy; sterilizace; Sterilization; artroplastiky kloubů; Polyethylenes; lidé; Ethylene Oxide; ethylenoxid; Vitamins; polyethyleny; Arthroplasty, Replacement; Humans